Redistribution and Insurance in the German Welfare State - Charlotte Bartels (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Welfare states redistribute both between individuals reducing annual inequality and over the life-cycle insuring against income risks. But studies measuring redistribution often focus only on a one-year period. Using German SOEP data from 1984 to 2009, long-term inequality over a 20-year period is computed and then decomposed into an inter- and intra-individual component. Results show that annual inequality is higher than long-term inequality, but redistribution is also larger annually. In the long-term, the German welfare state clearly gives priority to insurance over redistribution. This gets even more pronounced at later stages of the life-cycle through the payment of social security pensions.
Keywords: D31; D63; H53; H55; 330; Long-term income inequality; Income redistribution; Social security; Umverteilung; Soziale Sicherheit; Lebenseinkommen; Einkommensverteilung; Deutschland